Estudio del diagnóstico social en residencias para personas mayores asistidas en la Comunidad de Madrid: diseño de un instrumento de valoración y diagnóstico social - Cury, Silvia Patricia (Cuadernos de Trabajo Social, 2009)
The current article is the result of the research, developed by the authoress, within the framework of the Master in Communitary Social Work, Management and Assesment of Social Services, in the School of Social Work at the Complutense University de Madrid, along the academic year 2008-2009, and presented as the Final Report of Research, under the direction of the Professor Andrés Arias Astray. This report is based on the relevance of diagnosis, as a critical element of any social intervention, and its purpose is to make a methodological contribution in this field. Specifically, the survey was carried out about the status of the social diagnosis in nursing home of Madrid, and acording it’s results, a Social Diagnosis’Tool was developed, for it’s aplication in this intevention’s field. The intervention’s field’s choice responds to several factors, that detemine its relevance and appropiateness, at the present time, in assisted long term care. Among which one that stands out the implementation of the Protocols for Residential Care for the Elderly in Madrid, and the needs of social workers in this process of integration protocols, the current demographic situation in Spain and forecasts in this regard, a number growing older, the sociological changes occurring in the family institution, and therefore the challenge of care that these factors pose to care for the elderly in residential care.